2013
DOI: 10.1016/j.jped.2012.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric measures and blood pressure in school children

Abstract: Total body adiposity seems to be a better predictor of high blood pressure risk than abdominal fat in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 24 publications
7
32
2
2
Order By: Relevance
“…Validating other findings,31 we observed that elevated blood pressure was higher in overweight and obese children. Constanzi et al showed that schoolchildren with increased waist circumference were 2.8 times more likely to have high blood pressure levels than children with a normal waist circumference 27…”
Section: Discussionsupporting
confidence: 83%
“…Validating other findings,31 we observed that elevated blood pressure was higher in overweight and obese children. Constanzi et al showed that schoolchildren with increased waist circumference were 2.8 times more likely to have high blood pressure levels than children with a normal waist circumference 27…”
Section: Discussionsupporting
confidence: 83%
“…In a study of Brazilian adolescents ranging in age from 10 to 16 years, Moser et al 26 have shown that triceps skin-fold thickness and BMI represent anthropometric indicators independently associated with blood pressure above P90, irrespective of abdominal adiposity and sexual maturity. Furthermore, a high BMI increased the risk of high blood pressure nearly three-fold among students with excess body weight compared with eutrophic controls.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between high blood pressure and overweight is clearly defined in the existing literature; several studies have found that high BMIs 1,2,16,28 and high WCs 2,29 are associated with high blood pressure. Overall, in the reviewed studies, the risk of high blood pressure among schoolchildren with excess weight are elevated by between 1.50-and 4.9-fold 1,16,19,[27][28][29] . Furthermore, among students with WCs, the risk of high blood pressure is elevated by 3.84-fold 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in the municipality of Capão da Canoa (RS), the prevalence of overweight and obesity was significantly higher among the students whose fathers, mothers or both were obese. The risk of excess weight among schoolchildren with at least one parent who is overweight is increased by approximately 50% 27 . In a study conducted in Espirito Santo, schoolchildren with mothers with BMIs greater than 25.0 kg/m 2 were found to be at a 2.04-fold increased risk of excess weight 22 .…”
Section: Discussionmentioning
confidence: 99%